ATHENA: bowl chair / Nur Aisyah Annuar - Annuar, Nur Aisyah (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
ATHENA is a comfortable bowl chair designed with the inspiration of poppy flowers. The details such as petal shape and form were applied to the design. Not only that, but the colours also play an important characteristic of the design to make it look more elegant. The bowl chair is designed for users who wanted changes to their living room. With Athena, their living room could feel a lot different than usual. It is designed with poppy flower's unique characteristics, features, velvety and geometric shape as well as bright colours. The colour red was chosen to represent the poppy flower along with a little gold colour to make it look more balanced between the colours. In addition, hopefully, Athena will be a good product service for users in the future.